The phoenix of phonaesthetics: the rise of an old-new research paradigm on the beauty of language sound - Nemestothy, Lukas; Kogan, Vita V.; Reiterer, Susanne Maria (Frontiers in Psychology, 2025)
This review traces the historical, cultural, psychological, and neuroscientific dimensions of phonaesthetics—the study of beauty in language sound. Once considered too subjective or ideologically charged for serious inquiry, the aesthetics of language is now re-emerging as a vibrant interdisciplinary field that draws on linguistics, psychology, cognitive science, neuroscience, aesthetics, and literary studies. This review offers a structured synthesis of current debates, theories, and empirical findings, while also outlining methodological innovations, including bibliometric mapping. Contemporary research demonstrates that sound is not merely a transparent medium for meaning but an aesthetic phenomenon in its own right, shaping how language is learned, remembered, and valued. Advances in cognitive science, neuroaesthetics and psycholinguistics have given new empirical grounding to questions once considered marginal. From David Crystal’s early discussions to modern work on sound symbolism, memory, and brand naming, evidence consistently points to the interplay between inherent linguistic values and culturally imposed norms. While aesthetic preferences differ across speakers and contexts, recurring patterns—such as the appeal of sonorous or rhythmic structures—suggest shared cognitive and emotional mechanisms. At the same time, language ideologies and the familiarity effect continue to modulate responses, underscoring the multifaceted reasons for aesthetic judgment. Reviving phonaesthetics therefore means more than cataloguing pleasant sounds. It invites renewed inquiry into why sound matters, how it contributes to identity, shapes evaluations of linguistic varieties, and allows speech to be experienced as art. In this light, language deserves recognition alongside music, painting, and literature as a legitimate subject of aesthetic appreciation. This review aims to highlight that speech sound can elicit emotion as powerfully as melody or color. The “phoenix” of phonaesthetics thus rises again—not merely as a study of linguistic beauty, but as a call to reimagine language as one of the arts.